Increase in gunshot wounds at a level 1 trauma center following the COVID19 pandemic. Issue 4 (17th December 2021) - Padubidri, Anokha A.; Rushing, Amy; Ochenjele, George; Sontich, John; Napora, Joshua; Osborne, Ashli; Delozier, Sarah; Wetzel, Robert
Abstract: Objectives: To compare the number of patients with gunshot wounds presenting to our level 1 trauma center before and during the COVID-19 pandemic with a focus on volume trends after the lifting of stay-at-home directives through August 2020. Design: Retrospective. Setting: Level 1 trauma center. Patients/Participants: Seven hundred six gunshot wound patients between 2016 and 2020 (months March to September only). Intervention: COVID-19 pandemic and resultant stay at home directives. Main Outcome Measurements: Number of patients presenting with gunshot wounds per time period. Results: The number of patients with gunshot wounds presenting to our institution increased by 11.7% in March–April 2020 and by 67% in May–August 2020 when compared to previous years. Length of stay significantly decreased in 2020 compared to 2018 and 2019. In 2020, significantly fewer patients had orthopaedic procedures than in 2018. Conclusions: Patients presenting with gunshot wounds increased during the initial "stay-at-home" portion of the pandemic in March to April and increased significantly more after the restrictions were relaxed during May to August. Level of Evidence: Therapeutic Level III